HeartMate II pump exchange with HeartMate III implantation to the descending aorta. Issue 1 (30th December 2018) - Khayata, Mohamed; ElAmm, Chantal A; Sareyyupoglu, Basar; Zacharias, Michael; Oliveira, Guilherme H; Medalion, Benjamin
Abstract: Removal of the HeartMate II left ventricular assist device (LVAD) usually requires a sternotomy. We report a case of HeartMate III LVAD implantation to the descending aorta via a left thoracotomy while leaving most of the HeartMate II device in place to avoid redo‐sternotomy.